2021
DOI: 10.1021/acsbiomaterials.1c01267
|View full text |Cite
|
Sign up to set email alerts
|

Ovotransferrin Antibacterial Peptide Coupling Mesoporous Silica Nanoparticle as an Effective Antibiotic Delivery System for Treating Bacterial Infection In Vivo

Abstract: Antibiotic-resistant pathogens are a serious threat to global public health. The emergence of drug-resistant pathogens is due to the improper use of antibiotics, making the treatment of bacterial infections very challenging. Here, we reported an efficient antibiotic delivery nanoparticle to minimize antibiotic resistance. The nanoparticle was designed to target the bacterial membrane using mesoporous silica nanoparticles (MSNs) modified with an ovotransferrin-derived antimicrobial peptide (OVTp12), enabling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Recently, several antimicrobial agents such as polymeric cations, antimicrobial peptides, photodynamic or photothermal agents, quaternary ammonium-based compounds, , and inorganic NPs were reported. The rapid development in nanomaterials has set up a new ambit in the biomedical field and manifested possibilities in the research based on bacterial infections. Efforts are forged to generate green synthesized nanomaterials with different metals like zinc, copper, titanium, , gold, , and silver. , Among them, inorganic NPs (e.g., copper, silver, and gold NPs) brought new practicability in the development of efficient and safe antimicrobial agents. Especially, silver nanoparticles (AgNPs), an extensive antibacterial agent, , have recently fascinated much attention due to their excellent antimicrobial upshot on drug-resistant bacteria and auspicious germicidal potency in bacterial infections. , The silver ions (Ag + ) discharged from AgNPs play a pivotal role in antimicrobial activity , by enhancing the membrane permeability and producing reactive oxygen species (ROS) to damage cell walls. However, the tendency of aggregation of AgNPs and disturbance of Ag + release in the aqueous solution may diminish the antimicrobial efficiency of AgNPs during long-term use. , As a consequence, Ag-incorporated nanocomposites with high stability have aroused significant interest as bactericidal agents. ...…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several antimicrobial agents such as polymeric cations, antimicrobial peptides, photodynamic or photothermal agents, quaternary ammonium-based compounds, , and inorganic NPs were reported. The rapid development in nanomaterials has set up a new ambit in the biomedical field and manifested possibilities in the research based on bacterial infections. Efforts are forged to generate green synthesized nanomaterials with different metals like zinc, copper, titanium, , gold, , and silver. , Among them, inorganic NPs (e.g., copper, silver, and gold NPs) brought new practicability in the development of efficient and safe antimicrobial agents. Especially, silver nanoparticles (AgNPs), an extensive antibacterial agent, , have recently fascinated much attention due to their excellent antimicrobial upshot on drug-resistant bacteria and auspicious germicidal potency in bacterial infections. , The silver ions (Ag + ) discharged from AgNPs play a pivotal role in antimicrobial activity , by enhancing the membrane permeability and producing reactive oxygen species (ROS) to damage cell walls. However, the tendency of aggregation of AgNPs and disturbance of Ag + release in the aqueous solution may diminish the antimicrobial efficiency of AgNPs during long-term use. , As a consequence, Ag-incorporated nanocomposites with high stability have aroused significant interest as bactericidal agents. ...…”
Section: Introductionmentioning
confidence: 99%
“…These results show that mesoporous silica-delivered AMPs have advantages for the treatment of bacterial infections. [73] However, the coupling of peptides to their porous materials requires the consideration of various factors. For example, the study by Atefyekta et al also found that the matching between pore size and peptides is crucial.…”
Section: Porous Materials and Amp-based Conjugation Therapymentioning
confidence: 99%
“…Reproduced with permission. [ 73 ] Copyright 2022, American Chemical Society. B) Biodistribution of AMPs in mice.…”
Section: Abdominal Infectionmentioning
confidence: 99%
“…In addition, MSNs have a large surface area and a large porous volume, which improve the ability to load therapeutic cargo [ 132 , 133 ]. In a recent study by Ma and coworkers, the objective was to design an MSNs modified with an ovotransferrin-derived AMP that could act as a mechanism to interact with the bacteria and produce antimicrobial activities against them [ 134 ]. The amphipathic AMP OVTp12 was derived from egg white ovotransferrin, which displayed excellent antimicrobial activity through the disruption of the bacterial cell membrane [ 135 ].…”
Section: Amp-releasing Hydrogelsmentioning
confidence: 99%